Modification of Thin Film Composite Nanofiltration Membrane using Silver Nanoparticles: Preparation, Characterization and Antibacterial Performance - T. N. A., Tengku Sallehuddin; Mazrul Nizam, Abu Seman (Amirkabir University of Technology, Tehran, 2017)
This paper reports on preparation of polyamide membrane with addition of silver nanoparticles (AgNPs). AgNPs act as antibacterial agents that are less susceptible to membrane’s biofouling by interfacial polymerization (IP) method. AgNPs was synthesized via green route which has been reported previously. Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR), Field emission scanning electron microscopy (FESEM), contact angle measurement, and Energy dispersive X-ray spectrometer (EDX) were carried out to characterize the morphology of the prepared membrane samples. Inhibition zone of E. Coli bacteria was used to study the antibacterial behavior of the membranes. As a result, FTIR spectra clearly present the peak of primary amide, secondary amides, carboxyl group and etc. In addition, from the FESEM images, it could be seen that relatively regular and spherical shape AgNPs were formed. Contact angle results revealed that the PA membrane is more hydrophilic than that of the PES membrane. EDX spectra shows a peak that confirmed the presence of AgNPs on PA/Ag membrane. In antibacterial test, the PA membrane alone could not inhibit the growth of E.Coli. Membranes with 10 ml and 15 ml loading of AgNPs added to the M-Phenylenediamine (MPD) monomer for the IP process were not enough to kill the E.Coli bacteria. The addition of 20ml of AgNPs to MPD monomer however showed an interesting result as we can clearly observe the inhibition zone in the diameter of 1 mm around the circle of the membrane indicate that all bacteria were totally killed.